PT. Cassia Co-op: Perkembangan Perusahaan Pengolah Bahan Baku Kulit Manis di Kota Sungai Penuh (2012 – 2021) - Meliana Sofiani; Zul Asri (PAMA Aksara, 2023)
This research discusses how the development of PT. Cassia Co-op 2012-2021. PT. Cassia Co-op is the only company that processes raw cinnamon into finished goods, located in the village of Koto Dumo, Tanah Kampung District, Sungai Penuh City. This research is a qualitative research using historical research methods which are divided into four steps, namely heuristics, source criticism, interpretation, and historiography. Based on the research results, PT. Cassia Co-op is the only company that processes cinnamon in Sungai Penuh City. From its inception until now, PT. Cassia Co-op is experiencing very rapid development. This can be seen in terms of raw materials, capital, marketing, as well as the amount of production that continues to increase, labor and tools used in the production process which increase every year which are the supporting factors for the development of this company. In addition, the development of the company cannot be separated from the management and strategies used by the company so that the production process can run smoothly.